Work and Television - Giacomo Corneo (Center for Economic Studies and ifo Institute (CESifo), 2002)
In OECD countries watching television is by far the most time-consuming form of leisure. Surprisingly, television viewing is positively correlated with work hours across countries. A simple model based on the notion of aggregate strategic complementarities in social leisure is developed which explains such a pattern as resulting from multiple equilibria. Workers and capitalists are shown to exhibit opposite preference orderings over equilibria. The relative ability of those two groups in capturing a country's government may explain which equilibrium is selected.
Keywords: 330